Muammar Khadafi: Kepemimpinannya Dari Awal Kudeta Tak Berdarah Hingga Revolusi Berdarah Di Libya (1969-2011) - Afriyenti, Adinda; Humaidi, Humaidi (PERIODE: Jurnal Sejarah dan Pendidikan Sejarah, 2019)
Muammar Gaddafi is a figure destined to become the highest leader in Libya who comes from the descendants of the Qadaddfa tribe. Initially Gaddafi's political career began when he became Brotherly Leader of Jamahiriyah through a bloodless coup against monarch King Idris Sanusi's government on September 1, 1969 which later led Khadafi to become number one leader in Libya. During his leadership Gaddafi managed to make Libya an independent country without relying on other countries. However, the country he leads for 42 years is famous for Radical countries and shunned by other countries. The authoritarian nature of his leadership, invites the pros and cons of bringing his people against and undermining his leadership in 2011. Muammar Khadafi adalah sosok yang ditakdirkan untuk menjadi pemimpin tertinggi di Libya yang berasal dari keturunan suku Qadaddfa. Awalnya karir politik Khadafi dimulai ketika ia menjadi Brotherly Leader of Jamahiriyah melalui Kudeta tak berdarah terhadap pemerintahan monarki Raja Idris Sanusi pada 1 September 1969 yang kemudian mengantarkan Khadafi menjadi sosok pemimpin nomer satu di Libya. Selama kepemimpinannya Khadafi berhasil menjadikan Libya sebagai negara yang mandiri tanpa bergantung ke negara lain. Namun, negara yang dipimpinnya selama 42 tahun terkenal dengan negara Radikal dan dijauhi oleh negara lain. Sifat kepemimpinannya yang otoriter, mengundang pro dan kontra membawa rakyatnya menentang dan meruntuhkan kepemimpinannya pada tahun 2011.